“A ECONOMIA DAS TROCAS LINGÜÍSTICAS”, DE PIERRE BOURDIEU E “AS CATILINÁRIAS”, DE MARCUS TULLIUS CÍCERO: REFLEXÃO SOBRE A APLICABILIDADE DE UMA TEORIA SOCIOLÓGICA A UM TEXTO LATINO. - Garcia, Janete Melasso (Organon, 2012)
Marcus Tullius Cicero, born 106 B.C., has always been considered the greatest and mostcompetent orator that has ever lived. Pierre Bourdieu, a modern sociologist, has developed a theory aboutthe concept of broadened linguistic competence, stressing the necessary requirements for a speaker to beconsidered competent from the scientific point of view. The present article deals with the applicability ofBourdieu’s sociological theory, entitled : The Economy of Linguistic Exchanges”, to a Latin text by Cicero,with a view to confirming the pertinence of the ancient orator’s prestige.